Chronic Postoperative Pain After Primary and Revision Total Knee Arthroplasty. Issue 1 (January 2015) - Petersen, Kristian K.; Simonsen, Ole; Laursen, Mogens B.; Nielsen, Thomas A.; Rasmussen, Sten; Arendt-Nielsen, Lars
Abstract : Objectives: Clinical experience suggests that patients with osteoarthritis (OA) undergoing revision total knee arthroplasty (TKA) experience more chronic complications after surgery compared with patients receiving primary TKA. This study aimed to investigate the difference in pain, mobility, and quality of life (QoL) in patients after revision TKA compared with patients after primary TKA. Methods: A total of 99 OA patients after revision TKA surgery and 215 patients after primary TKA surgery were investigated in a cross-sectional study using: a pain description of current pain (non-existent, mild, moderate, severe, or unbearable), the pain intensity visual analogue scale, the Knee Society Score, and the Osteoarthritis Research Society International questionnaire. Results: Nineteen percent after primary TKA surgery and 47% after revision TKA surgery experienced severe to unbearable chronic postoperative pain. After revision TKA surgery patients reported higher pain intensities during rest ( P =0.039), while walking ( P =0.008), and on average over the last 24 hours ( P =0.050) compared with the patients after primary TKA surgery. Patients after revision TKA surgery had reduced walking distance ( P =0.001), increased use of walking aids ( P =0.015), and showed an overall decreased QoL ( P <0.001) compared with patients after primary TKA surgery. No significant improvement was found in walking distance ( P =0.448) for patients before revision TKA surgery compared with after revision TKA surgery. Discussion: More than twice as many patients have pain after revision surgery compared with patients after primary TKA. Patients after revision TKA surgery have reduced function, poorer QoL, and higher pain intensity compared with patients after primary TKA surgery.